2016
DOI: 10.1002/art.39562
|View full text |Cite|
|
Sign up to set email alerts
|

Diffuse Alveolar Hemorrhage Secondary to Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: Predictors of Respiratory Failure and Clinical Outcomes

Abstract: Objective. To identify predictors of respiratory failure and to evaluate the therapeutic efficacy of plasma exchange (PE) and of rituximab versus cyclophosphamide in a cohort of patients with diffuse alveolar hemorrhage (DAH) secondary to antineutrophil cytoplasmic antibody-associated vasculitis (AAV) with or without respiratory failure.Methods. We performed a single-center historical cohort study of all consecutive patients with AAVassociated DAH who were evaluated over a 16-year period. Logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 34 publications
8
79
2
9
Order By: Relevance
“…Intravenous methylprednisolone up to 500 mg every 6 hours for 4–5 days is recommended by most experts, although lower doses seem to have similar efficacy, followed by a gradual taper to maintenance doses of oral steroids [24]. Based on the severity of the disease, underlying etiology and organ involvement, plasma exchange or other immunosuppressive drugs such as cyclophosphamide, azathioprine, methotrexate, mycophenolate mofetil, etanercept may be indicated [25], [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous methylprednisolone up to 500 mg every 6 hours for 4–5 days is recommended by most experts, although lower doses seem to have similar efficacy, followed by a gradual taper to maintenance doses of oral steroids [24]. Based on the severity of the disease, underlying etiology and organ involvement, plasma exchange or other immunosuppressive drugs such as cyclophosphamide, azathioprine, methotrexate, mycophenolate mofetil, etanercept may be indicated [25], [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Fibreoptic bronchoscopy, particularly with BALF evaluation, is the best method to specifically diagnose DAH and for excluding other diseases [10]. Some studies of DAH patients with AAV showed that almost all patients have respiratory symptoms, such as dyspnoea and haemoptysis [3, 11, 12]. Additionally, DAH progresses rapidly and causes acute respiratory failure, such that the patients sometimes require admission to the Intensive Care Unit (ICU).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DAH progresses rapidly and causes acute respiratory failure, such that the patients sometimes require admission to the Intensive Care Unit (ICU). Cartin-Ceba et al reported that 34 of 73 patients with DAH secondary to AAV (47%) underwent mechanical ventilation (MV), and 41 patients (56%) were admitted to the ICU [11]. Moreover, DAH was reported to be an independent prognostic factor of MPA and the mortality rate of MPA patients with DAH is 8.65 times greater than that of MPA patients without DAH [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuere Daten zeigen jedoch keinen eindeutigen Nutzen der Plasmaseparation bei alveolärer Hämorrhagie [28]. Bei schwerer alveolärer Hämorrhagie kann zusätzlich eine Plasmaseparation erwogen werden.…”
Section: Diagnostikunclassified